THE CASE OF LITHUANIA AND BELGIUM: TEACHERS AND STUDENTS’ SOCIAL COMPETENCE - Gedviliene, Genute (European Scientific Journal, ESJ, 2014)
Social competence is very important to people in seeking their goals, and it becomes more and more complicated, requiring better knowledge and skills. It is evident that a basic challenge for Europe may become not technologies or business skills but social competence. It can be reached through learning. Educational environment is understood as a complex of learning process, personality of a teacher, learning methods, technologies, means, interreaction of learners. Otherwise, learning is conceived as a social phenomenon where knowledge is gained by sharing, cooperation and communication. Purposeful and attractive learning can take place in any institution (family, school, university, etc.) group or community. Life changes determine new ideas, more effective theories on learning and finding new educational methods. Cooperation and collaboration is described as the basis of social competence. It is clear that social competence is revealed through learning and other activities. So it is vitally important for young people, striving for independence and becoming a competent citizen. Otherwise, social competence forms necessary skills in fighting challenges, keeping friendly relations, seeking effective learning, joining community or group activity. Using learning methods, are compared Belgian and Lithuanian students‘ and teachers‘ interreaction in learning environment.